Amyloid imaging in mild cognitive impairment subtypes - Wolk, David A.; Price, Julie C.; Saxton, Judy A.; Snitz, Beth E.; James, Jeffrey A.; Lopez, Oscar L.; Aizenstein, Howard J.; Cohen, Ann D.; Weissfeld, Lisa A.; Mathis, Chester A.; Klunk, William E.; DeKosky, Steven T. (Annals of neurology, 2009)
Objective We utilized the amyloid imaging ligand Pittsburgh Compound B (PiB) to determine the presence of Alzheimer's disease (AD) pathology in different mild cognitive impairment (MCI) subtypes and to relate increased PiB binding to other markers of early AD and longitudinal outcome. Methods Twenty‐six patients with MCI (13 single‐domain amnestic‐MCI [a‐MCI], 6 multidomain a‐MCI, and 7 nonamnestic MCI) underwent PiB imaging. Twenty‐three had clinical follow‐up (21.2 ± 16.0 [standard deviation] months) subsequent to their PiB scan. Results Using cutoffs established from a control cohort, we found that 14 (54%) patients had increased levels of PiB retention and were considered “amyloid‐positive.” All subtypes were associated with a significant proportion of amyloid‐positive patients (6/13 single‐domain a‐MCI, 5/6 multidomain a‐MCI, 3/7 nonamnestic MCI). There were no obvious differences in the distribution of PiB retention in the nonamnestic MCI group. Predictors of conversion to clinical AD in a‐MCI, including poorer episodic memory, and medial temporal atrophy, were found in the amyloid‐positive relative to amyloid‐negative a‐MCI patients. Longitudinal follow‐up demonstrated 5 of 13 amyloid‐positive patients, but 0 of 10 amyloid‐negative patients, converted to clinical AD. Further, 3 of 10 amyloid‐negative patients “reverted to normal.” Interpretation These data support the notion that amyloid‐positive patients are likely to have early AD, and that the use of amyloid imaging may have an important role in determining which patients are likely to benefit from disease‐specific therapies. In addition, our data are consistent with longitudinal studies that suggest a significant percentage of all MCI subtypes will develop AD. Ann Neurol 2009;65:557–568